1991
DOI: 10.2307/2275474
|View full text |Cite
|
Sign up to set email alerts
|

Decomposing Baire functions

Abstract: We discuss in the paper the following problem: Given a function in a given Baire class, into “how many” (in terms of cardinal numbers) functions of lower classes can it be decomposed? The decomposition is understood here in the sense of the set-theoretical union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 4 publications
0
37
0
Order By: Relevance
“…It is easy to see that for each > 0 the set of points at which the oscillation 6 of E * is greater than must be a closed discrete set. Hence E * is of Baire class 1 on its domain.…”
Section: Definition 22 a Set E ⊆ Rmentioning
confidence: 99%
See 1 more Smart Citation
“…It is easy to see that for each > 0 the set of points at which the oscillation 6 of E * is greater than must be a closed discrete set. Hence E * is of Baire class 1 on its domain.…”
Section: Definition 22 a Set E ⊆ Rmentioning
confidence: 99%
“…In [6] the authors consider the following question: If A and B are two families of functions between Polish spaces, what is the least cardinal κ such that every member of A can be decomposed into κ members of B -this cardinal κ the authors call dec (A, B). The most natural class to consider for B is the class of continuous functions and the problem to which it gives rise had been posed by Lusin, who wondered whether every Borel function could be decomposed in countably many continuous functions.…”
Section: Decomposing Continuous Functionsmentioning
confidence: 99%
“…We will write Π κ for Π κ (R). In [4] the authors considered the following cardinal decomposition function for arbitrary families F ⊂ R Z , with Z ⊂ R, and G ⊂ {R X : X ⊂ Z}:…”
Section: Preliminariesmentioning
confidence: 99%
“…In [4] the authors considered the values of dec(B β , B α ) for α < β < ω 1 , where B α stands for the functions of α-th Baire class. In particular, they proved that where cov(M) is the smallest cardinality of a covering of R by meager sets, and d, the dominating number, is the smallest cardinality of a dominating family D ⊂ ω ω , that is, such that for every f ∈ ω ω there exists g ∈ D such that f ≤ * g. Moreover, in papers [12] and [11] it has been proved that each of these inequalities can be strict.…”
Section: Preliminariesmentioning
confidence: 99%
“…Laczkovich showed that for any 1 ≤ β < ω 1 there is an f ∈ L β with dec(f, B β ) > ω (see [CM] for a proof); and by [CMPS,Theorem 5.5] there is an f ∈ L 1 that is f lower semicontinous, with dec(f, B 1 ) ≥ cov (M). The next corollary improves on these results.…”
Section: S Lawomir Soleckimentioning
confidence: 99%